Pengantar editorial MediaPsi 10 (1) 2024 - Akhrani, Lusy Asa (Universitas Brawijaya, 2024)
This introduction provides an overview of the contributions included in this MediaPsi edition. There are six articles in Mediapsi 10(1) 2024. One article is in English and the other five are in Indonesian. The six articles in Mediapsi 10(1) 2024 depict a range of life phenomena in people, from young children to adults. People undergo a range of experiences that result in a range of reactions, including both maladaptive and adaptive behavior. In three articles, research findings are presented against the backdrop of adaptive behavioral phenomena, such as the selfless actions of blood donors, teenagers' subjective well-being, and students' sustainable behavior. In contrast, three other articles review research findings beginning with maladaptive phenomena, such as postpartum depression, child sexual abuse, and divorce that may arise from different conflict resolution approaches. The diversity of articles featured in Mediapsi's first issue of 2024 is expected to stimulate theoretical and practical contributions to upcoming studies.